Multiple-surface sliding mode control for 3DOF helicopter - Hamood, Mostafa A.; Akmeliawati, Rini; Legowo, Ari (2011)
The three degree of freedom (3DOF) helicopter is a simplified model, which is used to study the behaviours of the helicopters. It is an example of a so-called underactuated mechanical system that has a fewer control inputs than degrees of freedom. Application of multiple-surface sliding mode control to such model looks attractive, because of the ability of this method to stabilize the underatuated systems and to deal with uncertainties, which usually exist in such systems. In this paper, a multiple-surface sliding mode is proposed to control the elevation and travel angles of the 3DOF helicopter.